English and indonesian code-mixing in novel "marriage of convenience"(a sociolinguistic perspective) - Dyah Rismawati, Rizki (2016)
This research aims to 1) identifying the types of code mixing in novel "Marriage of Convenience" and 2) explaining the motives of using code mixing in novel "Marriage of Convenience". In this research, the researcher uses a descriptive qualitative as the type of the research. The object of the study is code mixing found in Marriage of Convenience novel. The data of this research are word, phrases, and sentences that containing code mixing of English and Indonesian in Marriage of Convenience novel. The researcher uses documentation to collect the data then coding the code mixing found in Marriage of Convenience novel. The results show that first there are 670 data, 426 data or 63.58% belong to insertion, 227 data or 33.88% belong to alternation, and 17 data or 2.54% belong to congruent lexicalization. On the category of insertion, there are four types of insertion such as 241 data belonging to insertion of word, 23 data belonging to insertion of hybrid, 6 data belonging to insertion of word reduplication, and 156 data belonging to insertion of phrases. On the category of alternation, there are two types of alternation such as 3 data belonging to alternation of clause and 224 data belonging to alternation of sentence. The majority of the type of code mixing that the researcher found in Marriage of Convenience novel is insertion (63.58%). The second results show that there are 57 data or 8.51% belong to need filling motive and 613 data or 91.49% belong to prestige filling motive. The majority of motive of using code mixing that the researcher found is prestige filling motive (91.49%). The data are analyzed by using Muysken's theory for the types of code mixing and Hoccket's theory for the motives of using code mixing.